Extraction and characterization of acetic acid-soluble collagen and papain-soluble collagen hydrolysate from poultry eggshell membrane - Ma, Roazita (2016)
Collagens have unique biocompatible and biodegradable properties that are widely used in food, cosmetics, and biomedical applications. However, collagen derived from land-based animals pose problems as a risk to transmissible disease as Bovine Spongiform Encephalopathy (BSE) and footand- mouth diseases, the risk of autoimmune and allergic reaction in its biomedical applications, and skepticism amongst faith-based niche market particularly for Muslims and Jewish consumers. Collagen extracted from eggshell membrane was thus proposed as an alternative. Extraction efficiency and characterization of collagen of acetic acid-soluble collagen (ASC) and papain-soluble collagen hydrolysates (PSCH) from eggshell membrane were investigated. Studies were carried out under three variables (enzyme concentration, temperature, and pH), it was found that the most efficient conditions for ASC was at 15 °C, pH 3, with a yield of 0.23% on a dry weight basis, while PSCH was at 15 °C, pH 3 and enzyme concentration of 300K U/g of raw material with a yield of 0.55% on a dry weight basis. The isoelectric points of ASC and PSCH were found to be at pH 6.61 and 6.89, respectively. The FTIR spectra of both ASC and PSCH demonstrated similar absorption bands to that of porcine. The maximum transition temperature of ASC and entropy were observed at 61.84°C and 0.139 J/g, whilst PSCH was at 59.12°C and 0.046 J/g, indicating such thermal profile was almost at the par of the mammalian thermal profile. The color determination of ASC revealed that it had bright intensity of lightness, low intensity of redness and yellowness, whilst the colour determination of PSCH revealed that it had a slightly higher intensity of redness. ASC in 0.5 M acetic acid had high solubility till pH 3 and then remain relatively stable till pH 10, whilst PSCH in 0.5 M acetic acid had high solubility till pH 4 then remain relatively stable to pH 10. For the effect of NaCl concentration on collagen solubility, ASC demonstrated a distinguishable decrease in solubility especially at concentrations above 2% and then decreased slightly at above 4%, whilst PSCH demonstrated drastic decrease at 3% and remain steady at above 4%. The odor patterns of ASC displays a low intensity, PSCH revealed that it had considerable intensity of odor which require careful consideration in its application.